Volatile Constituents in Mosses (Brachythecium albicans (Hedw.) Schimp., Bryum pallescens Schleich. ex Schwagr and Syntrichia intermedia Brid.) Grown in Turkey - Ozdemir, Turan; Ucuncu, Osman; Beyza Cansu, Tayyibe; Kahriman, Nuran; Yayli, Nurettin (Asian Journal of Chemistry, 2010)
The essential oils of mosses [Brachythecium albicans (Hedw.) Schimp., Bryum pallescens Schleich. ex Schwagr and Syntrichia intermedia Brid.] have been investigated by GC and GC/ MS. The main compounds found in the oils of B. albican, were nonanal (41.0 %) and 4,4- dimethyl-E-2-pentene (6.6 %). The major components identified in the oils of B. pallescens, were nonanal (29.3 %) and Z-phytol (8.9 %). E-2-tetradecen-1-ol (9.9 %) and nonanal (8.3 %) were the main compounds found in the oil of S. intermedia. The essential oils of B. albican, B. pallescens and S. intermedia were rich in aldehydes (51.3, 41.7 and 18.0 %), hydrocarbons (13.5, 7.9 and 24.1 %) and alcohols (4.3, 9.2 and 13.5 %), respectively. The amounts of terpenoids present in the investigated mosses are generally less than non-terpenoid compounds.